Factores de riesgo para caries dental en infantes de 6 a 36 meses atendidos en la Clínica del Niño, Facultad de Odontología, Universidad Nacional Mayor de San Marcos 2007 - Castañeda Mosto, María (2011)
The aim of the study was to determine risk factors for dental caries in infants treated at the Child Clinic in 2007 (oral hygiene habits, dietary habits and how microbial transmissibility (mother - child). Prior informed consent of parents, we selected 73 infants from 6 to 36 months with carious lesions in deciduous teeth, a dental record data were collected for analysis of risk factors. The clinical examination determined the presence of white spot and cavitated lesions. It was clearly noted the influence of risk factors (oral hygiene of the infant, direct microbial transmissibility mother-child and diet), in the presence of dental caries in its two stages: white spot and cavitated lesions. It is concluded that the identified risk factors favoring the appearance of dental caries in infants, so it is necessary the first visit to the dentist before the first year of life, in this way would be imparted educational and preventive programs (binomial mother - child) to improve their quality of life.